'I want (to be) an active grandmother' – activity as a new normative framework of subjective meanings and expectations associated with the grandmother role. Issue 8 (22nd March 2018) - MARHÁNKOVÁ, JAROSLAVA HASMANOVÁ
ABSTRACT: The article analyses the norms of grandmothering in relation to cultural representations of active ageing. Based on interviews that were carried out with 20 mothers and 20 grandmothers of children under the age of ten, the article focuses on the way in which the current emphasis on activity influences ideas about how the roles of grandparent should be performed and how women relate to their own ageing. The analysis shows that being active represented a significant framework of the mothers' notions and expectations associated with care provided by grandmothers, of grandmothers' talk about their own grandparental role and how both generations of women interpret their own memories of their own grandmothers. Both the mothers and the grandmothers noted how the family role of grandmothers had changed compared to past generations of grandmothers. This change was framed by the idea of having an active lifestyle and this idea formed an important framework for the mothers' expectations about what their role as grandmothers might be like in the future. This paper critically analyses those representations of the grandmother role and point out the emergence of new forms of conflicts and challenges, and the sense of ambivalence about traditional roles that result from the close association made between being active and the representation of grandmothering.